A cross-sectional observation on maximal eccentric hamstring strength in 7- to 15-year-old competitive Alpine skiers - Kiers, K.; Ellenberger, L.; Javet, M.; Bruhin, B.; Frey, W. O.; Spörri, J. (Biology, 2021)
Competitive alpine skiing is a sport with frequent occurrence of severe knee injuries, and it is well known that the hamstring muscles play an important role in preventing these injuries. The aim of this study was to assess the maximal strength capacity for braking, the downward movement during Nordic Hamstring Exercises, the so called maximal eccentric hamstring strength, in 7- to 15-year-old skiers. Absolute strength values were greater in skiers under 15 years old (U15) skiers than in those under 10 years old (U10), as well as in U15 males compared to their female counterparts. There were no sex differences in U10 skiers. Absolute strength values were generally dependent on age and biological developmental stage, but this dependence was considerably attenuated when body weight was considered. This should be kept in mind when testing athletes around the growth spurt. Abstract Severe knee injuries are common in alpine skiing and the hamstring muscles are known to counteract the anterior tibial displacement that typically accompanies major injury mechanisms. This study aimed to assess the Maximal Eccentric Hamstring Strength (MEHS) of youth competitive alpine skiers during Nordic Hamstring Exercise (NHE) in terms of dependence of sex, age and biological maturation. A total of 246 7- to 15-year-old skiers were tested with respect to their MEHS using an NHE-based measurement device (Vald Performance, Newstead, Australia). Significantly greater absolute MEHS was observed in skiers of the under 15 years (U15) category compared to skiers under 10 years old (U10) (227.9 ± 61.1 N vs. 142.6 ± 28.9 N; p < 0.001), also when grouped by sex. Absolute MEHS was revealed to be lower in U15 females compared to males (213.5 ± 49.0 N vs. 241.9 ± 68.4 N; p = 0.001); in U10 skiers there was no sex difference. For all age groups and sexes, absolute MEHS values were significantly correlated with age and biological maturation (p < 0.001). However, when normalized to body weight such associations disappeared, which is why this is strongly recommended when testing around their growth spurt. Overall, this study established sport-specific normative reference data that may be of interest to researchers and sport practitioners alike.